2019
DOI: 10.3390/cells8080857
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Adipocytes on the Regulation of Breast Cancer in the Tumor Microenvironment: An Update

Abstract: Obesity is a global pandemic and it is well evident that obesity is associated with the development of many disorders including many cancer types. Breast cancer is one of that associated with a high mortality rate. Adipocytes, a major cellular component in adipose tissue, are dysfunctional during obesity and also known to promote breast cancer development both in vitro and in vivo. Dysfunctional adipocytes can release metabolic substrates, adipokines, and cytokines, which promote proliferation, progression, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
89
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(91 citation statements)
references
References 189 publications
(238 reference statements)
1
89
0
1
Order By: Relevance
“…Hypertrophic and hyperplastic adipocytes through their metabolic substrates, such as both saturated and unsaturated fatty acids (FAs) and matrix metalloproteinase (MMPs), regulate breast cancer biology. FAs are stored as lipid droplet in the adipose tissue and their release, induced by highfat diet and obese status, may contribute to angiogenesis and inflammation, key steps of tumor development and progression (47). Mostly, FAs can activate toll-like receptor 4 and NF-kB/TNF-α signaling.…”
Section: Breast Cancer Tumor Microenvironment and Adipose Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…Hypertrophic and hyperplastic adipocytes through their metabolic substrates, such as both saturated and unsaturated fatty acids (FAs) and matrix metalloproteinase (MMPs), regulate breast cancer biology. FAs are stored as lipid droplet in the adipose tissue and their release, induced by highfat diet and obese status, may contribute to angiogenesis and inflammation, key steps of tumor development and progression (47). Mostly, FAs can activate toll-like receptor 4 and NF-kB/TNF-α signaling.…”
Section: Breast Cancer Tumor Microenvironment and Adipose Tissuementioning
confidence: 99%
“…Moreover, adipocytes produce molecules, defined as "released hormones, " including estrogens and adipokines. In post-menopausal obese patients, the elevated level of estrogens, produced by aromatase highly expressed in adipocytes, activates ERα, promoting breast cancer cell growth and progression (47). Furthermore, changes in adipokines profile, due to the altered fat distribution and function, is one of the main features in obese state.…”
Section: Breast Cancer Tumor Microenvironment and Adipose Tissuementioning
confidence: 99%
“…This is achieved by the activation of different pathways including mTOR and NF-K B signaling in the breast cancer cells. Unfortunately, this antitumor effect is diminished in obesity due to reduced expression of adiponectin receptors leading to therapy resistance [75]. Controversially, other studies have shown that adiponectin can stimulate breast cancer migration and growth [76,77].…”
Section: Adipocytes As Regulators Of Bone Metastasesmentioning
confidence: 99%
“…Controversially, other studies have shown that adiponectin can stimulate breast cancer migration and growth [76,77]. In contrast, leptin has a protumor effect and is associated with increased metastasis [75,78]. For example, adipocyte-derived leptin and IL-1β increase breast cancer cell colonization and migration to the adipose tissue adipocytes of the skeleton [79].…”
Section: Adipocytes As Regulators Of Bone Metastasesmentioning
confidence: 99%
See 1 more Smart Citation